Mathematics for physicists - Martin, B. R.; Shaw, G. 1942- (Wiley, 2015)
Mathematics for Physicists is a relatively short volume covering all the essential mathematics needed for a typical first degree in physics, from a starting point that is compatible with modern school mathematics syllabuses. Early chapters deliberately overlap with senior school mathematics, to a degree that will depend on the background of the individual reader, who may quickly skip over those topics with which he or she is already familiar. The rest of the book covers the mathematics that is usually compulsory for all students in their first two years of a typical university physics.
Includes bibliographical references and index. - Print version record and CIP data provided by publisher
Keywords: Mathematics; Mathematical physics; Mathématiques; Physique mathématique; MATHEMATICS; Essays; MATHEMATICS; Pre-Calculus; MATHEMATICS; Reference